How can the unnaturalness of cellular agricultural products be familiarized?: Modeling public attitudes toward cultured meats in Japan - Hibino, Aiko; Nakamura, Futoshi; Furuhashi, Mai; Takeuchi, Shoji (Frontiers in Sustainable Food Systems, 2023)
This study aims to clarify how the unnaturalness of cellular agricultural products can be familiarized to society, using the case of the Japanese public’s receptivity to cultured meats. Perceived unnaturalness is a key factor in the rejection of emerging technologies. While past studies have examined the explanatory factors involved in the public acceptance of cultured meats, the relationships among multiple factors have not been fully examined. Cultured meats and cellular agricultural products have been positively evaluated because they can contribute to future food sustainability, so the trade-off between perceived unnaturalness and sustainability is a significant issue for the public. This study uses a questionnaire survey with 2,000 Japanese respondents, which was conducted in 2019. Using a categorical data analysis approach, the strongest explanatory factors for receptivity were comprehensively searched among attitudes toward cultured meats, eating habits, demographics, and so on. The results indicated that perceived unnaturalness showed a strong explanatory power for the rejection of cultured meats, but the combination of perceived unnaturalness and awareness of world famine problems depicted a stronger explanation. The perceived animacy of non-human life forms is also associated with an interest in cultured meats, which may reflect Japanese cultural values. These results suggest multiple pathways to overcoming the disgust of new food technologies in the social implementation process.